Perancangan Aplikasi Pengarsipan Surat Berbais Web pada PT. Perkebunan Nusantara IV Medan - Rakha, Riyan Hidayat; Samsudin, Samsudin (Jurnal Ilmiah Sains dan Teknologi, 2024)
Archiving is the task of storing highly important data. All recorded data must be accurate and accessible whenever needed, enabling employees to provide effective services. Manual archiving of letters often leads to errors in data storage and retrieval. Therefore, there is a need for a web-based letter archiving application system to address these issues. This research employs the waterfall method, where the developed system is web-based using HTML, Xampp, MySQL manages the database, and PHP programming language is utilized with the assistance of Visual Studio Code text editor. The goal of this research is to design an archiving system that can be managed effectively and efficiently. Letter archiving is done electronically, where documents are stored in softcopy form and equipped with incoming and outgoing letter reports. This approach reduces the risk of errors in data storage and letter retrieval, as the data is stored in a computer database.